(untitled) (Journal of economic and management development research, 2025)
As a crucial representation of new quality productive forces and a national strategic emerging industry, the high-quality development of the low-altitude economy is inseparable from the deep integration and empowerment of digital technology. Zhengzhou, as a national central city, has leveraged its “dual-zone overlay” strategic advantages to form a preliminary industrial ecosystem and application scale in the low-altitude economy. However, it also faces challenges such as uneven coverage of digital infrastructure, low marketization of data elements, shortage of technology and talent, and insufficient synergy in institutional mechanisms. Based on a review of relevant research and practices at home and abroad, this paper systematically analyzes the development foundation, digital advantages, and existing problems of Zhengzhou’s low-altitude economy. Subsequently, it proposes systematic countermeasures and suggestions, including building an “air-space-ground integrated” digital foundation, deepening the integration of “low-altitude + digital” scenarios, constructing a “technology-data-manufacturing” empowerment chain, and improving the digital ecosystem and institutional safeguards. This aims to provide theoretical references and practical pathways for Zhengzhou to seize digital opportunities and promote the higher quality, more efficient, and more sustainable development of its low-altitude economy.